Effects of treatment with gold nanoparticles in a model of acute pulmonary inflammation induced by lipopolysaccharide. Issue 1 (1st October 2019) - dos Santos Haupenthal, Daniela Pacheco; Mendes, Carolini; de Bem Silveira, Gustavo; Zaccaron, Rubya Pereira; Corrêa, Maria Eduarda Anastácio Borges; Nesi, Renata Tiscoski; Pinho, Ricardo Aurino; da Silva Paula, Marcos Marques; Silveira, Paulo Cesar Lock
Abstract: The bacterial lipopolysaccharide (LPS) is a highly toxic molecule derived from the outer membrane of gram‐negative bacteria. LPS endotoxin affects the lungs and is used as a model of acute pulmonary inflammation affecting the cellular morphology of the organ. Previously, gold nanoparticles (GNPs) have been shown to demonstrate anti‐inflammatory and antioxidative activity in muscle and epithelial injury models. The objective of this study was to investigate the effect of the intraperitoneal treatment using GNPs on the inflammatory response and pulmonary oxidative stress induced by LPS. Wistar rats were divided into four groups ( N = 10): Sham; Sham + GNPs 2.5 mg/kg; LPS; and LPS + GNPs 2.5 mg/kg. Treatment with LPS upregulated the levels of markers of cellular and hepatic damage (CK, LDH, AST, and alanine aminotransferase); however, the group treated with only GNPs exhibited no toxicity. Treatment with GNPs reversed LPS‐induced changes with respect to total peritoneal leukocyte count and the pulmonary levels of pro‐inflammatory cytokines (IFN‐γ and IL‐6). Histological analysis revealed that treatment with GNPs reversed the increase in alveolar septum thickness due to LPS‐induced fibrosis. In addition, treatment with GNPs decreased production of oxidants (nitrite and DCFH), reduced oxidative damage (carbonyl and sulfhydryl), and downregulated activities of superoxide dismutase and catalase. Treatment with GNPs did not showed toxicity; however, it exhibited anti‐inflammatory and antioxidative activity that reversed morphological alterations induced by LPS.